أثر استخدام إستراتيجية الأمواج المتداخلة في التحصيل والتنور العلمي عند طلاب الصف الأول المتوسط في مادة الإحياء - كطران رائد بايش (lark, 2019)
• The aim of the research is to know the impact of Overlapping waves strategy in Biology subject Achievement and Scientific lighting of Intermediate first class StudentThe researcher uses the experimental design of a partial disciple with two equal groups, experimental and control. In according to this design, a sample which is represented by (Al-NAWARS) School for Boys which belongs to the Directorate of Education of (THEEQAR)and the number of the sample (60) Student.The researcher matches between the two groups in the following variables: age, the parents’ education, former education, and test the above information. The behavioural purposes for these chapters are drafted which consist of(155) purposesas well as the researchers have prepared (18) teaching plan for each of the experimental and control groups, with regard to Find researchers mayor to build the two tools Search represented by the test achievement in the material component of the biology of (40) substantive paragraph of the check type multiple-ever four alternatives The second tool scientific literacy component of (44) paragraph scale and after the application of the two tools research and analysis of the results showed the results: • There is a statistical difference between the experimental and control group in the achievement variable for experimental group. • There is a statistical difference between the experimental and control group in the Scientific lighting variable for experimental group. According to these results ,the researcher concluded that relying on the interfered waves strategy has a great positive influence in Achievement and the Scientific lighting. The researcher recommended with many recommendations such as: relying on the interfered Overlapping waves strategy in teaching Biology subject, moreover the researcher suggested to make another studies for different stages and Curricula to recognize its effectiveness in other variables.